2016
DOI: 10.1016/j.jcmg.2015.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Measures of Ventricular-Arterial Coupling and Circumferential Strain Predict Cancer Therapeutics–Related Cardiac Dysfunction

Abstract: Structured Abstract Objective The objective of this study was to determine the relationships between echocardiography-derived measures of myocardial mechanics and cancer therapeutics-related cardiac dysfunction (CTRCD). Background Doxorubicin and trastuzumab are highly effective breast cancer therapies, but have a substantial risk of CTRCD. There is a critical need for the early detection of patients at increased risk of toxicity. Methods We performed a prospective, longitudinal cohort study of breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 34 publications
7
88
0
1
Order By: Relevance
“…While a number of prior investigations in tertiary care centres have suggested a role for myocardial mechanics in cardio-oncology,13 22–25 our data provide external validity to the relevance of non-invasively derived measures of myocardial mechanics to community-based populations treated with anthracyclines. Moreover, our findings emphasise the critical importance of assessing change over time in imaging measures with cancer therapy.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…While a number of prior investigations in tertiary care centres have suggested a role for myocardial mechanics in cardio-oncology,13 22–25 our data provide external validity to the relevance of non-invasively derived measures of myocardial mechanics to community-based populations treated with anthracyclines. Moreover, our findings emphasise the critical importance of assessing change over time in imaging measures with cancer therapy.…”
Section: Discussionsupporting
confidence: 52%
“…Our prior data in a tertiary-referral breast cancer population first suggested that Ea, Ea/Ees sb as well as longitudinal and circumferential strain and strain rate hold important diagnostic and prognostic relevance 13. This current study suggests that these indices are also valid in community-based populations.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…While EF is an adequate gross marker of cardiac function, it may not be sensitive enough to detect early cardiac dysfunction [13][14][15]. Zito et al demonstrated that there is enough variability in EF measurements that it is not sensitive to detect a decrease in EF less than 10% [7].…”
Section: Echocardiographymentioning
confidence: 99%